Análisis de factibilidad de un sistema de Telecomunicaciones mediante la tecnología Wimax para el cantón Guano. - Pazmiño Moreno, Mónica Fernanda (2013)
This project pretends to show a way to get to provide telecommunication services to areas of difficult where access other technologies that have not been implemented due to topography or location of these sectors. The project shows the feasibility analysis and design of a telecommunications system using WiMAX technology (Worldwide Interoperability for Microwave Access) for the Canton Guano, which made a detailed analysis of technology analyzing 802.16 service features, range of coverage, spread, technology, spectrum availability, architecture and standards.